2014
DOI: 10.1111/clr.12454
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation on the surface of modern implant abutment materials

Abstract: Within the limitations of a laboratory study, the results suggest that biofilm formation on the surface of PEEK is equal or lower than on the surface of conventionally applied abutment materials such as zirconia and titanium. However, clinical studies are necessary to corroborate these preliminary results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
141
4
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(165 citation statements)
references
References 20 publications
10
141
4
10
Order By: Relevance
“…Material wear leads to surface roughness promoting biofilm formation. Hahnel et al investigated this process on PEEK, zirconia and titanium surfaces and found equal or less biofilm formation on PEEK surface [34]. The wear behavior of a resin-based CAD/CAM-nanocomposite and even a direct nanocomposite material was not significantly different from that of human enamel [36].…”
Section: Discussionmentioning
confidence: 99%
“…Material wear leads to surface roughness promoting biofilm formation. Hahnel et al investigated this process on PEEK, zirconia and titanium surfaces and found equal or less biofilm formation on PEEK surface [34]. The wear behavior of a resin-based CAD/CAM-nanocomposite and even a direct nanocomposite material was not significantly different from that of human enamel [36].…”
Section: Discussionmentioning
confidence: 99%
“…Five were clinical reports [2,6,8,18,24] and 35 were papers on PEEK surface treatments [13][14][15][16][17] how the bioactivity of PEEK can be improved [1,21]; the characteristics of CFR-PEEK [3,7,[19][20]; the biocompatibility of PEEK [5]; PEEK applications [4,8,[10][11]30]; PEEK biofilm formation [22,[31][32][33][34], PEEK as an abutment material and as an implant material [12,23,[25][26][27][28][29]35,40] and the use of CAD-CAM with PEEK [36][37][38][39]. …”
Section: Literature Search and Resultsmentioning
confidence: 99%
“…It has been reported that PEEK, compared with titanium, presented the lowest BIC [31][32]. To achieve good bioactivity, many modifications for pure PEEK have been proposed [1,[3][4]9,14,[17][18][19][20][21][22].…”
Section: Bic-types Of Peekmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Bununla birlikte in-vitro çalışma-larda titanyum dayanakların kırılma dayanımının zirkonya dayanaklardan yüksek olduğu bildirilmiştir. 19,25,28 Uygun bir bağlantı tasarımı, dikkatle kontrol edilmiş bir oklüzyon ve de iyi planlanmış restorasyonlar uzun dönemde zirkonya dayanakların klinik başarısı için gereklidir. Üretim Şekillerine Göre Dayanaklar…”
Section: Zirkonya Dayanaklarunclassified